Low electric charge loading in a sequencing batch electro-membrane bioreactor: influence of aeration intensity on treatment performance, biomass activity, and membrane fouling - Tiago José Belli; Emerson Souza; Caroline Rodrigues; André Aguiar Battistelli; Wanderli Leite; Miriam Cristina Santos Amaral; Flávio Rubens Lapolli (Environmental Science and Pollution Research, 2026)
This study investigates the performance of a sequencing batch electro-membrane bioreactor (SB-EMBR) operated under low electric charge loading (39.9 mAh L⁻ 1 ), focusing on the effects of aeration intensity on treatment performance, biomass activity, and membrane fouling. The reactor was operated at a current density of 10 A m −2 and three specific aeration demand levels (SADₘ = 0.48, 0.24, and 0.12 m 3 m⁻ 2 h⁻ 1 ). Organic matter and phosphorus removals remained consistently high (> 90% COD removal; TP < 1.0 mg L⁻ 1 ) regardless of aeration intensity. In contrast, ammonium removal efficiency declined from 99.5 to 74.7% as the SADₘ decreased from 0.48 to 0.12 m 3 m⁻ 2 h⁻ 1 . Batch assays revealed reduced activity of polyphosphate-accumulating organisms under oxygen-limited conditions. The pronounced decrease in the P-release/COD-uptake ratio from 0.172 to 0.0164 mol P mol⁻ 1 C indicates that TP removal at low dissolved oxygen became predominantly governed by chemical coagulation rather than the biological phosphorus removal process. The calculated Al/P molar ratio of 2.32 mol Al mol⁻ 1 P was sufficient to sustain phosphorus removal through both precipitation and adsorption onto aluminum hydroxides. Reduced aeration favored anoxic phosphorus uptake, increasing the denitrifying phosphate assimilation potential from 18 to 41%. The membrane fouling rate increased from 1.02 to 4.81 kPa d⁻ 1 as aeration decreased, mainly due to diminished shear forces, soluble microbial products accumulation (+ 205%), floc size reduction (− 50.1%), and higher capillary suction time (+ 123%). Owing to the short current application (1.6 h d⁻ 1 ), the additional electrocoagulation cost was only 0.07 USD m⁻ 3 , lower than values reported for continuous-flow EMBRs. Overall, operation of the SB-EMBR under reduced electric charge loading demonstrated promising energy efficiency while maintaining stable and satisfactory pollutant removal even at low aeration intensities.